NEED FOR APPRECIATION IN RAJKUMAR HIRANI'S 3 IDIOTS MOVIE (2009): A HUMANISTIC PSYCHOLOGICAL APPROACH - SARI, SRI MARTONO LANJAR (2011)
The major problem of this study is the need for appreciation reflected in Rajkumar Hirani‟s 3 Idiots movie (2009). The purpose of the research is to analyze the movie based on the structural elements of 3 Idiots movie 2009 and to describe the struggle of appreciation of Ranchoddas "Rancho" Shamaldas Chanchad, Farhan Qureshi, and Raju Rastogi in getting their appreciation based on the humanistic psychological perspective. The type of the research is qualitative. The object of the study is 3 Idiots Story movie directed by Rajkumar Hirani and publishing by Vidhu Vinod Chopra in 2009. The primary data source is 3 Idiots Story movie itself and the secondary data sources are the other sources related to the movie. The method of collecting data is the library research. The technique of data analysis is descriptive analysis. Based on analysis, the study shows the following conclusions. Firstly, based on the structural analysis indicated that each of narrative and technical element is interrelated to each other. Secondly, based on the humanistic psychological analysis depicts three people who struggle and prove their appreciation. Need for appreciation is prominent thing in this story.